2022
DOI: 10.1111/nyas.14816
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐21‐5p functions via RECK/MMP9 as a proalgesic regulator of the blood nerve barrier in nerve injury

Abstract: Both nerve injury and complex regional pain syndrome (CRPS) can result in chronic pain. In traumatic neuropathy, the blood nerve barrier (BNB) shielding the nerve is impaired-partly due to dysregulated microRNAs (miRNAs). Upregulation of microRNA-21-5p (miR-21) has previously been documented in neuropathic pain, predominantly due to its proinflammatory features. However, little is known about other functions. Here, we characterized miR-21 in neuropathic pain and its impact on the BNB in a human-murine back tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
(110 reference statements)
0
8
0
Order By: Relevance
“…Plus, Leinders et al [ 75 ] evaluated a cohort of patients that suffered from neuropathic pain from different etiologies; in them the authors found that miR-21-5p expression is significantly higher in white blood cells and the sural verve of patients with polyneuropathies. In a more recent study, Reinhold et al [ 76 ] found that patients with complex regional pain syndrome (CRPS), as well as a rodent model of neuropathic pain, presented a significant higher expression of miR-21-5p; the authors concluded that this miRNA is a major switch in neuropathic pain due to its role in affecting pain behavior through different pathways, including inflammation-independent barrier impairment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plus, Leinders et al [ 75 ] evaluated a cohort of patients that suffered from neuropathic pain from different etiologies; in them the authors found that miR-21-5p expression is significantly higher in white blood cells and the sural verve of patients with polyneuropathies. In a more recent study, Reinhold et al [ 76 ] found that patients with complex regional pain syndrome (CRPS), as well as a rodent model of neuropathic pain, presented a significant higher expression of miR-21-5p; the authors concluded that this miRNA is a major switch in neuropathic pain due to its role in affecting pain behavior through different pathways, including inflammation-independent barrier impairment.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, an indirect modulation of claudin-1 in long COVID can also be hypothesized; by means of the modulation of matrix metalloprotease-9 (MMP-9), an important regulator of axon demyelination and extension [ 105 ]; MMPs are predominantly expressed in Schwann cells of peripheral nerves under normal conditions and are upregulated in peripheral nerve injury [ 106 , 107 ]. Several miRNAs of the ones here reviewed exert direct or indirect modulation of MMP-9; miR-21-5p has been shown to impair BNB integrity by inhibiting RECK, giving rise to MMP-9 and further downregulating claudin-1 [ 108 ]; plus, a direct induction of MMP-9 expression by miR-21-5p was also shown [ 76 ]. In the present review, the levels of miR-21-5p were divided between being down- and upregulated; the former could be associated with a mechanism of protection and the latter with pathogenic one.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, using WT and RECK mutant NSCLC cells treated with SC exosomes, we also revealed that mutated non‐functional RECK with a blocked ability to interact with exosomal miR‐21‐5p completely counteracted activation of tumor cell motility and invasiveness induced by SC exosomes. Interestingly, RECK targeting by miR‐21 was implicated in neuropathic pain independent of prior inflammation (Reinhold et al, 2022). Hypoxia may also increase miR‐21‐5p delivery by bone‐marrow‐derived mesenchymal stem cell‐secreted exosomes and promote lung cancer development by reducing apoptosis and promoting macrophage M2 polarization (Ren et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, expression of microRNA-21-5p (miR-21) was elevated in plasma of patients with complex regional pain syndrome and in nerves of mice exposed to nerve injury. Mice presented with BNB leakage and loss of claudin-1 in injured and spared nerves [ 145 ]. Additionally, RECK gene, a putative target of miR-21, was decreased, as was downstream Mmp9 and Tgfb was upregulated in the nerves.…”
Section: Peripheral Events In the Pathophysiology Of Ptnpmentioning
confidence: 99%
“…Additionally, RECK gene, a putative target of miR-21, was decreased, as was downstream Mmp9 and Tgfb was upregulated in the nerves. These findings suggest that the effect of miR-21 on pain-like behavior are exerted via the inhibition of REC, the rise in MMP9 and, ultimately, claudin-1 downregulation [ 145 ]. Therefore, miR-21 was proposed to play a major role in neuropathic pain and affects pain-like behavior through different pathways, including inflammation-independent barrier impairment.…”
Section: Peripheral Events In the Pathophysiology Of Ptnpmentioning
confidence: 99%